Investigation of Steam Blanching and Infrared Drying in Processing of Chrysanthemum indicum L. Flower Herbal Tea - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2019)
In Vietnam, Chrysanthemum indicum has been used as an herb. Its flower has a strong aroma. Chrysanthemum indicum L. flower has a bright yellow color and various functional active compounds. However it’s easily perishable in blooming season, it’s necessary to to dry fresh Chrysanthemum indicum L. flower to extend its shelf‐life for long-term use. Objective of this study penetrated on the effectiveness of various processing variables such as blanching by steaming; infrared drying power, temperature and time on total phenolic, flavonoid, carotenoid and sensory score of dried herbal tea from Chrysanthemum indicum flowers by the infrared irradiation. Our results showed that these flowers should be blanched by steaming within 60s and then being dried at power 200 W, temperature 60oC with air velocity 1.5 m/s in the infrared dryer. From this approach, major phytochemical components such as total phenolic, flavonoid, carotenoid in the dried Chrysanthemum indicum flower could be maintained. Owing to the benefits of the infrared irradiation, it would be an innovative solution for blanching and drying to preserve utmost valuable elements inside as well as good appearance outside of dried Chrysanthemum indicum L. flower.Keywords: Chrysanthemum indicum, Steaming, Drying, Infrared irradiation, Phenolic, flavonoid, Carotenoid.